The Beneficial Role of Anchomanes difformis in STZ-Induced Reproductive Dysfunction in Male Wistar Rats - Alabi TD (Dove Medical Press, 2020)
Toyin Dorcas Alabi,1 Charon de Villiers,2 Stephan S du Plessis,3 Thomas K Monsees,4 Nicole L Brooks,5 Oluwafemi Omoniyi Oguntibeju1 1Phytomedicine & Phytochemistry Group, Oxidative Stress Research Centre, Department of Biomedical Sciences, Faculty of Health and Wellness Sciences, Cape Peninsula University of Technology, Bellville, South Africa; 2PUDAC-Delft Animal Facility, South African Medical Research Council, Cape Town 7505, South Africa; 3Division of Medical Physiology, Faculty of Medicine and Health Sciences, Stellenbosch University, Tygerberg 7505, South Africa; 4Department of Medical Biosciences, University of the Western Cape, Bellville 7535, South Africa; 5Faculty of Health and Wellness Sciences, Cape Peninsula University of Technology, Cape Town, South AfricaCorrespondence: Oluwafemi Omoniyi Oguntibeju Tel +27 219538495Email oguntibejuo@cput.ac.zaBackground: Progression of diabetes mellitus has increasingly led to several diabetic complications. Diabetes is one of the major factors implicated in male reproductive system damage. Recent approaches such as the use of medicinal plants have been explored in the management of diabetes and associated complications. Anchomanes difformis (common name: children’s umbrella) has been shown to possess anti-diabetic ability in animal model. Therefore, this study seeks to investigate the potency of Achomanes difformis in ameliorating diabetes-induced reproductive dysfunction.Methods: Type 2 diabetes was induced in male Wistar rats with 10% fructose administration for 2 weeks and an intraperitoneal injection of 40mg/kgBW of streptozotocin. Aqueous extract (200mg and 400mg/kgBW) of Anchomanes difformis leaves was administered daily for 6 weeks. The rats were randomly divided into 7 groups with a minimum of eight rats in each (8 rats in normal groups and 10 in diabetic groups). The impact of diabetes and treatment was investigated by estimating sperm concentration, motility indices, viability and morphological parameters in the normal, treatment controls and diabetic rats using CASA-SCA system. Histological examination of the testes and epididymis was performed.Results: Diabetes induction resulted in significant decrease in sperm concentration, viability and some motility parameters with 40% abnormalities in sperm morphology. The administration of Anchomanes difformis significantly increased sperm concentration and sperm viability, while it significantly improved the percentage of morphologically normal sperm in diabetic rats. Anchomanes difformis ameliorated testicular damage such as vacuolization and loss of germinal epithelium in the diabetic-treated rats when compared to the diabetic controls.Conclusion: The potency Anchomanes difformis displayed against diabetic-induced damage in the reproductive system might be a new and promising tool in the management of male reproductive dysfunctions and associated complications in diabetes mellitus.Keywords: Anchomanes difformis, diabetes mellitus, male fertility, sperm function